An exploratory perspective on the practice of ritual behaviors as a means of psychological preparation among football players - Imad Eddine MEGA; Abderrafik BENDERRADJI; Abdelmalek GUERRAD (Pensées Genre, Penser Autrement)
The study aims to identify and determine the forms of ritual practices among football players and to reveal the reasons and motivations behind players resorting to these practices. It also seeks to understand the players' opinions and beliefs regarding the impact and functions of these practices on their behavior during competition. The study sample consists of 41 football players. We used the descriptive method, and the results indicate that players tend to engage in religious-based rituals to a very high degree, often practicing them individually and privately. In addition to religious rituals, players also highly engage in routine rituals (such as chants, motivational gatherings...), while they avoid practicing non-religious rituals (such as superstitions, charms, etc.). Uncertainty, anxiety, and a strong desire for achievement and control over situations are among the main reasons and motivations for practicing rituals. Moreover, players believe that ritual practices have a positive impact on their behavior, helping them control their emotions and increase their focus during competition. Keywords: Rituals, Psychological Preparation, Football, Ritual, motivations.